From precision synthesis to cross-industry applications: The future of emerging peptide technologies - Mingming Wang; Hongmin Xia; Cheng Wang; Tong Zhang; Mengru Zhang; Xinyi Li; Chune Peng; Tianyuan Jing; Yuwei Wang; Lizeng Peng; Ping Wang (Pharmacological Research)
Peptides, derived primarily from natural bioactive sources, play essential roles in human physiological processes such as hormone regulation and nerve signal transmission. Recent advances in phage display technology have revolutionized peptide screening, enabling the rapid and efficient identification of billions of peptide within a single day. The integration of artificial intelligence (AI) has further accelerated peptide discovery, allowing for the swift identification of bioactive sequences and structural optimization to enhance their stability, efficacy, and target specificity. Peptides have demonstrated extensive applications across diverse industries. In medicine, they exhibit potent antibacterial, antiviral, and antitumor properties, with antimicrobial peptides (AMPs) emerging as promising alternatives against multidrug-resistant bacteria. In the food industry, peptides contribute to functional foods by providing antihypertensive, antioxidant, and immunomodulatory effects, promoting overall health. The cosmetics sector also relies on peptides for their ability to stimulate collagen production, enhance skin regeneration, and deliver anti-aging benefits, making them key ingredients in advanced skincare formulations. Emerging delivery nanocarrier systems, aim to improve peptide stability, absorption, and half-life. With ongoing technological breakthroughs and interdisciplinary collaboration, peptides are poised to play an increasingly pivotal role in modern medicine and biotechnology, offering innovative solutions for a range of health, food, and cosmetic applications.